E-Mortality using Agile Scrum Method to Improve Information Services Effectiveness - Ardafa Ihromi; Yuda Syahidin; Erix Gunawan; Neneng Yuniarty (Universitas Bumigora, 2023)
The advancement of information system technology is presently used extensively in many disciplines, including the field of health care or hospitals. This research aims to create an information system to handle hospital data to facilitate the processing patient data that has been declared dead with quality. In this study, it was found that there was no information system in the form of a program or application to handle death data. The management process still relies on Microsoft Excel, considered less efficient. In addition, the development of this information system is assisted by choosing the suitable software development methodology and considering existing needs. This research uses the Agile Development Method with the Scrum framework for software development. This research is qualitative descriptive and uses the observation method in data collection. C# programming language and MySQL database are also used in this system. This research produces an information system to handle death data by the product backlog. It is intended to meet user needs to assist in processing death data more effectively and efficiently and reduce the error rate associated with recording death data manually.